Biological control of Fusarium oxysporum f. sp. phaseoli by Trichoderma harzianum and its use for common bean seed treatment - Carvalho, Daniel Diego Costa (2014)
Biological control of seed-borne pathogens has shown to enhance germination and physiological quality of seeds. The objectives of this study were to evaluate the in vitro antagonistic effect of five Trichoderma harzianum isolates (CEN287, CEN288, CEN289, CEN290, and CEN316) against Fusarium oxysporum f. sp. phaseoli (Foxy) and test its potential use in seed treatment. Initially, pathogen and antagonists were grown in paired cultures at 25ºC, from which samples were assessed using scanning electron microscopy (SEM). Then, clean or Foxy-infected seeds were treated with conidial suspension of the antagonists. Percent of Foxy-infected seeds and normal seedlings were evaluated at seven and nine days of incubation, respectively. All but one Trichoderma isolate (CEN290) inhibited Foxy mycelial growth. SEM analysis revealed that only one Trichoderma isolate (CEN287) showed parasitic interaction with Foxy. Two isolates (CEN287 and CEN316) significantly reduced the Foxy incidence and enhanced seed germination, though less effective than the fungicide mixture (carboxin + thiram). A principal component analysis indicated the importance of volatile metabolites in reducing Foxy incidence on common bean seeds. CEN287 Trichoderma harzianum isolate formed a single group due to its increase in germination rate of Foxyinfected seeds.